Convergent Evolution of Slick Coat in Cattle through Truncation Mutations in the Prolactin Receptor - Porto-Neto, Laercio R.; Bickhart, Derek M.; Landaeta-Hernandez, Antonio J.; Utsunomiya, Yuri T.; Pagan, Melvin; Jimenez, Esbal; Hansen, Peter J.; Dikmen, Serdal; Schroeder, Steven G.; Kim, Eui-Soo; Sun, Jiajie; Crespo, Edward; et al. (Frontiers in Genetics, 2018)
Evolutionary adaptations are occasionally convergent solutions to the same problem. A mutation contributing to a heat tolerance adaptation in Senepol cattle, a New World breed of mostly European descent, results in the distinct phenotype known as slick, where an animal has shorter hair and lower follicle density across its coat than wild-type animals. The causal variant, located in the 11th exon of prolactin receptor, produces a frameshift that results in a truncated protein. However, this mutation does not explain all cases of slick coats found in criollo breeds. Here, we obtained genome sequences from slick cattle of a geographically distinct criollo breed, namely Limonero, whose ancestors were originally brought to the Americas by the Spanish. These data were used to identify new causal alleles in the 11th exon of the prolactin receptor, two of which also encode shortened proteins that remove a highly conserved tyrosine residue. These new mutations explained almost 90% of investigated cases of animals that had slick coats, but which also did not carry the Senepol slick allele. These results demonstrate convergent evolution at the molecular level in a trait important to the adaptation of an animal to its environment.